1999
DOI: 10.1088/0953-4075/32/22/305
|View full text |Cite
|
Sign up to set email alerts
|

Total and state-selective electron capture cross sections for C3++H collisions

Abstract: Abstract. Electron capture cross sections in collisions of C 3+ ions with atomic hydrogen have been studied using the close-coupling two-centre atomic orbital (AO) expansion method by treating the collision system in a quasi-two-electron model. Total electron capture cross sections to the dominant individual singlet and triplet excited states are calculated over the energy range 0.1-50 keV amu −1 . The results are compared with existing experimental data and with theoretical calculations based on the molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
3
8
0
Order By: Relevance
“…Comparison of the present result with the other theoretical data shows good agreement with Errea et al [8] at intermediate energies and with Tseng and Lin [7] at larger energies. The Errea et al [8] calculations are based on the molecular-orbital expansion method in the impact parameter formalism that employs classical, straight-line trajectories for the nuclei.…”
Section: B the C 3+ Ionsupporting
confidence: 90%
See 3 more Smart Citations
“…Comparison of the present result with the other theoretical data shows good agreement with Errea et al [8] at intermediate energies and with Tseng and Lin [7] at larger energies. The Errea et al [8] calculations are based on the molecular-orbital expansion method in the impact parameter formalism that employs classical, straight-line trajectories for the nuclei.…”
Section: B the C 3+ Ionsupporting
confidence: 90%
“…They can also have different orbital parts and evolve differently in time as well. The HF SCF orbitals used in this analysis are [24,25], and the theoretical results of Errea et al [8], Tseng and Lin [7], Bienstock et al [26], and Heil et al [27] are also shown. molecular orbitals of the ion-hydrogen molecule combined when the nuclei are close together and asymptotically become the 3p orbitals of the Si 2+ ion.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…This is supported by the close agreement of the calculations of refs. [226,228] with each other and, where available, with experimental data as well. Overall, figure 15 illustrates nicely that an uncertainty estimate for a complicated collision problem should use the input from several calculations based on different theoretical methods.…”
Section: Charge Transfer Collisionsmentioning
confidence: 99%